2000
DOI: 10.1785/0120000026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Manual and Automatic Onset Time Picking

Abstract: The onset times for 78 teleseismic iP phases are picked by four seismic analysts and by three automatic picking algorithms, on both the single trace and on an array beam. The difference in the onset times picked by different analysts is on average ‫760.0ע‬ sec with a standard deviation of 0.15 sec. The analysts on average pick times 0.1 sec earlier on the beam than on the single trace.The three automatic pickers are the picker described by Earle and Shearer (1994), an autoregressive-Akaike information criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 9 publications
(5 reference statements)
2
59
0
1
Order By: Relevance
“…For the AR-model picker of Win system, both the forward and backward AR models (Takanami and Kitagawa, 1988;Leonard, 2000) are used to derive the AIC. The result of the AR-model picker is also shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the AR-model picker of Win system, both the forward and backward AR models (Takanami and Kitagawa, 1988;Leonard, 2000) are used to derive the AIC. The result of the AR-model picker is also shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Algorithms based on wavelet analysis (Anant and Dowla, 1997;Zhang et al, 2003) and polarization analysis (Vidale, 1986;Reading et al, 2001) have also been suggested. The most commonly used algorithm is the autoregressive (AR) model (Yokota et al, 1981;Maeda, 1985;Takanami and Kitagawa, 1988;Sleeman and Eck, 1999;Leonard and Kennett, 1999;Leonard, 2000). Methods using the autoregressive model are based on the assumption that seismograms can be divided into two locally stationary intervals at the time of an arrival of seismic signal, with each interval satisfying a different autoregressive process.…”
Section: Introductionmentioning
confidence: 99%
“…This estimate is frequently a very good approximation of the arrival time (e.g. Leonard, 2000) with the significance of the AIC minimum increasing with increasing contrast in the amplitude and spectral content between the signal and noise. In the absence of a signal onset hypothesis, we can simply perform this procedure on consecutive overlapping segments of the seismogram, calculating short AIC traces at regular intervals (e.g.…”
Section: Strategies For Characterizing Repeating Sources and Aftershocksmentioning
confidence: 99%
“…When the order of the AR process is fixed, the AIC function is a measure for the model fit. The point where the AIC is minimized determines the optimal separation of the two stationary time series in the least squares sense, and thus is interpreted as the phase onset (Sleeman and van Eck, 1999); this picker is known as AR-AIC picker (Leonard, 2000). Different than AR-AIC picker, calculates the AIC function directly from the seismogram without using the AR coefficients.…”
Section: Akaike Information Criterion (Aic) Pickermentioning
confidence: 99%